Optimisation of Nitrogen Plasma Exposure Time for Surface Modification of Cotton Fibre - Ainul Hafiza Abdul Hair; Kushairi Mohd Salleh; Nyak Syazwani Nyak Mazlan; Mohamad Khalid Khairunnisa Atiqah; Noorain Purhanudin; Anin Sofya Mohd Akhiri; Sarani Zakaria; Rozidawati Awang (BioResources, 2024)
Surface modification via plasma treatment is useful in improving textile-based wound dressing functionality. This study was conducted to optimise the nitrogen plasma exposure time and its effect on the cotton surface (CS) properties at a constant nitrogen flow rate of 20 sccm for 5 to 30 min. The optimisation was done by analysing the alteration in morphology, functional group composition, crystallinity phase, electrokinetic charge, and colour of CS as subjected to nitrogen plasma. CS experienced an etching effect due to the presence of microcracks on its surface, with its electrokinetic charge becoming less negative, ranging from -5.51 to -1.32 mV. Then, the nitrogen functional group was detected on CS ranging from 2.9% to 4.5%, with its whiteness index reduced to 8.67% compared to the pristine cotton. As a result, 20 min was selected as the optimum exposure time for surface treatment because the exposure time of 30 min showed an early sign of degradation, which reduced its crystallinity index by 11.1%. Apparently, activated CS experienced slight changes in its molecular structure without affecting its bulk properties. Thus, the plasma-modified CS is useful in creating a biocompatible wound dressing that can anchor therapeutic biomaterial and improve healing.